Implementasi Metode Mengajar Convergent dan Divergent untuk Meningkatkan Kebugaran Jasmani serta Motivasi Belajar Pendidikan Jasmani pada Siswa SMPN 2 Sakra - Ma'ripatullah; Syah, Herman; Muhammad Salabi; Muhaimin, Ali (Empiricism Journal, 2025)
This study aims to examine the effect of convergent and divergent teaching styles on physical fitness and learning motivation of eighth grade students of SMPN 2 Sakra. Based on the main hypothesis, it is expected that there will be significant differences in the improvement of physical fitness and learning motivation between the two teaching styles, both independently and through interaction with the gender variable. The method used was a 2x2 factorial experiment with a sample of 96 students, divided evenly into convergent and divergent groups, and measured through pre-test and post-test physical fitness including 60 m running, sit-ups, pull-ups, and vertical jumps, as well as a Likert-scale learning motivation questionnaire. The results of the Two-Way ANOVA analysis showed that teaching style did not significantly affect changes in physical fitness scores (p > 0.05), but the convergent style showed a tendency to maintain more stable physical performance. Conversely, there was a significant effect of teaching style on learning motivation (p < 0.05), where the convergent style increased student commitment and focus, while the divergent style maintained enthusiasm through freedom of exploration. Analysis of gender effects revealed significant differences in post-test physical fitness between male and female students (p < 0.05), while differences in learning motivation based on gender were not significant. The interaction between teaching style and gender was only significant for physical fitness (p < 0.05), indicating different responses across demographic groups, but not for learning motivation.